2015
DOI: 10.1159/000439424
|View full text |Cite
|
Sign up to set email alerts
|

Primary Plasma Cell Leukemia in the Era of Novel Agents: A Multicenter Study of the Japanese Society of Myeloma

Abstract: We investigated the treatment and outcome of Japanese patients with primary plasma cell leukemia (pPCL) in the era of novel agents and analyzed the risk factors affecting survival. Among 3,318 patients with symptomatic multiple myeloma (MM), 38 patients were diagnosed with pPCL. The median overall survival (OS) of the pPCL patients was 2.85 years, which was significantly extended compared with that in previous reports. The proportion of patients treated with novel agents was 61%. The OS of the patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…During the last decades, initially autologous stem cell transplantation 9 (ASCT) and subsequently novel therapies 10 including immunomodulatory drugs and proteasome inhibitors (PIs) namely bortezomib, led to a slight improvement of pPCL patients’ survival 5 . The efficacy of bortezomib in pPCL has been demonstrated by our group and others in small retrospective series 5 , 11 13 , however, this has been questioned in other studies 14 , 15 . Recently, a prospective phase 2 study has demonstrated that induction therapy with bortezomib based combinations followed by ASCT led to high response rates and prolonged survival in patients with pPCL 16 .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…During the last decades, initially autologous stem cell transplantation 9 (ASCT) and subsequently novel therapies 10 including immunomodulatory drugs and proteasome inhibitors (PIs) namely bortezomib, led to a slight improvement of pPCL patients’ survival 5 . The efficacy of bortezomib in pPCL has been demonstrated by our group and others in small retrospective series 5 , 11 13 , however, this has been questioned in other studies 14 , 15 . Recently, a prospective phase 2 study has demonstrated that induction therapy with bortezomib based combinations followed by ASCT led to high response rates and prolonged survival in patients with pPCL 16 .…”
Section: Introductionmentioning
confidence: 78%
“…The introduction of first generation novel agents, i.e., thalidomide, lenalidomide, and bortezomib has improved response rates and OS 20 of MM patients, therefore it was reasonable to explore their role in PCL 4 , 5 . Novel agent-based therapies and more commonly bortezomib-based combinations were evaluated retrospectively in several case reports and case series, that included limited number of patients, as expected, considering the rarity of the disease 5 , 11 13 ; according to those studies, objective response ranged from 56-80% and median OS ranged from 12–31 months, depending on the incorporation or not of ASCT in the induction therapy 5 , 11 13 . We have previously suggested that, the efficacy of bortezomib could be at least partially related to abnormal CD27 expression whose triggering on pPCL cells has a significant anti-apoptotic effect involving ERK1/2, NF-kB, and JNK signal transduction pathways 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Iriuchishima et al. reported that novel agents significantly prolonged OS compared to other treatments (2.85 versus 1.65 years, p = 0.049) [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Acta Haematologica , Iriuchishima et al [3] report a national retrospective Japanese survey concerning 38 cases of PPCL collected over a 12-year period. In this study, there was no difference in overall response rates (ORR) to ‘conventional' or novel therapies (68 vs. 67%), but significantly higher rates of complete response and very good partial response were detected in patients treated with novel agents (50 vs. 16%; p = 0.029).…”
mentioning
confidence: 99%